Site directed mutagenesis to improve E. Coli phytase activity for animal feed - Samsudin, Nurhusna; Gad, Abd El-Aziem Farouk; Mohd. Salleh, Hamzah (INSI Publications, 2012)
Phytate is largely unavailable to monogastric animal such as swine, poultry and fish, as they lack of sufficient endogenous enzymatic activity to hydrolyze phytate. The result is the elimination of precious nutrients that would be beneficial to their growth; furthermore, they will excrete most of the indigestive phytate which can contribute to phosphorus being over applied to the land. Phosphorus has a beneficial impact on vegetative growth on land as well as marine vegetation, causing an increased growth of weeds. This enhanced vegetation consumes large amounts of oxygen, resulting in the loss of aquatic life and ultimately contributes to water pollution and eutrophication of ground water and aquatic environment. Phytase, a type of histidine acid phosphatase hydrolyzes phytin phosphorus and when present in an animal's digestive tract, benefits the animal while reducing total phosphorus levels in manure. Computer modeling has been used to identify and examine the active site of phytase. The factors influencing the ligand binding strength in the active site were analyzed and computational site directed mutagenesis experiments were carried out to evaluate the effects of mutations on the binding strength before and after mutation. From the directive results of computational studies, point mutation was introduced by site directed mutagenesis using polymerase chain reaction (PCR). The activity was measured by kinetic characterization with phytate as a substrate. Decrease in KM notable in all functional mutants indicates that all mutant shows increment in substrate binding. Two functional mutants showed improvement in phytase activity and thermostability.